Photon Upconverted Circularly Polarized Luminescence via Triplet–Triplet Annihilation. Issue 45 (19th December 2018) - Yang, Dong; Han, Jianlei; Liu, Minghua; Duan, Pengfei
Abstract: Circularly polarized luminescent materials are of increasing attention due to their potential applications in advanced optical technologies, such as chiroptical devices and optical sensing. Recently, in all reported circularly polarized luminescent materials, high‐energy excitation results in low‐energy or downconverted circularly polarized luminescence (CPL) emission. Although photon upconversion—i.e., the conversion of low‐energy light into higher‐energy emission, with a wide variety of applications—has been widely reported, the integration of photon upconversion and CPL in one chiral system to achieve higher‐energy CPL emission has never been reported. Herein, a brief review is provided of recent achievements in photon‐upconverted CPL via the triplet–triplet annihilation mechanism, focusing on the amplified dissymmetry factor g lum through energy transfer process and dual upconverted and downconverted CPL emission through chirality and energy transfer process. Abstract : Upconverted circularly polarized luminescence (UC‐CPL) via triplet–triplet annihilation‐based photon upconversion in chiral systems is an emerging topic in photochemistry and photophysics. The concept of this topic is described, and recent advances in the construction and application of UC‐CPL materials are highlighted. In addition, new functions emerging from UC‐CPL materials are presented.